Ticlopidine-, Clopidogrel-, and Prasugrel-Associated Thrombotic Thrombocytopenic Purpura: A 20-Year Review from the Southern Network on Adverse Reactions (SONAR) - Jacob, Sony; Dunn, Brianne L.; Qureshi, Zaina P.; Bandarenko, Nicholas; Kwaan, Hau C.; Pandey, Dilip K.; McKoy, June M.; Barnato, Sara E.; Winters, Jeffrey L.; Cursio, John F.; Weiss, Ivy; Raife, Thomas J.; Carey, Patricia M.; Sarode, Ravindra; Kiss, Joseph E.; Danielson, Constance; Ortel, Thomas L.; Clark, William F.; Rock, Gail; Matsumoto, Masanori; Fujimura, Yoshihiro; Zheng, X. Long; Chen, Hao; Chen, Fei; Armstrong, John M.; Raisch, Dennis W.; Bennett, Charles L. (Seminars in Thrombosis and Hemostasis, 2012)
Thienopyridine-derivatives (ticlopidine, clopidogrel, and prasugrel) are the primary antiplatelet agents. Thrombotic thrombocytopenic purpura (TTP) is a rare drug-associated syndrome, with the thienopyridines being the most common drugs implicated in this syndrome. We reviewed 20 years of information on clinical, epidemiologic, and laboratory findings for thienopyridine-associated TTP. Four, 11, and 11 cases of thienopyridine-associated TTP were reported in the first year of marketing of ticlopidine (1989), clopidogrel (1998), and prasugrel (2010), respectively. As of 2011, the FDA received reports of 97 ticlopidine-, 197 clopidogrel-, and 14 prasugrel-associated TTP cases. Severe deficiency of ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) was present in 80% and antibodies to 100% of these TTP patients on ticlopidine, 0% of the patients with clopidogrel-associated TTP (p < 0.05), and an unknown percentage of patients with prasugrel-associated TTP. TTP is associated with use of each of the three thienopyridines, although the mechanistic pathways may differ.
Keywords: thrombotic thrombocytopenic purpura; ticlopidine; clopidogrel; prasugrel; adverse event